2008
DOI: 10.1109/ipdps.2008.4536287
|View full text |Cite
|
Sign up to set email alerts
|

DiCo-CMP: Efficient cache coherency in tiled CMP architectures

Abstract: Future CMP designs that will integrate tens of processor cores on-chip will be constrained by area and power. Area constraints make impractical the use of a bus or a crossbar as the on-chip interconnection network, and tiled CMPs organized around a direct interconnection network will probably be the architecture of choice. Power constraints make impractical to rely on broadcasts (as Token-CMP does) or any other brute-force method for keeping cache coherence, and directory-based cache coherence protocols are cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…This prediction based on previous recent history is similar to the one proposed by Martin et al [52]. Other works also benefit from this observation with different aims [7,65,66].…”
Section: Read-only Data Optimizations and Full-adaptivitysupporting
confidence: 70%
“…This prediction based on previous recent history is similar to the one proposed by Martin et al [52]. Other works also benefit from this observation with different aims [7,65,66].…”
Section: Read-only Data Optimizations and Full-adaptivitysupporting
confidence: 70%
“…However, these traditional cache coherence protocols introduce indirection in the critical path of cache misses [13]. To solve the problem of indirection, Token-CMP [14] and DiCo-CMP [15] protocols have been proposed. These indirection-aware protocols avoid the access to the home node allowing latency of cache misses to be reduced.…”
Section: Related Workmentioning
confidence: 99%
“…Among these are: Tagless directories [43] from Zebchuk et al, demonstrated to be highly area-efficient but not energyscalable; SCI [20] from James et al, using sharer pointers in the private caches rather than a directory structure; token coherence [27] from Martin and Hill, also avoiding a coherence directory; software-controlled address indirection by Fensch and Cintra [14] and Hardavellas et al [19] handle coherence in software on shared cache substrates; and DiCo [32] from Ros et al, eliminating directories in favor of storing coherence information within the cache tags.…”
Section: Related Workmentioning
confidence: 99%